Enhancing the Anaerobic Response - DOLFERUS, RUDY (Ann Bot, 2003)
Proteome analysis, and more recently DNA chip technology, has led to the identification of a large number of genes that are implicated in the anaerobic response of plants. As a result, an increasingly complex picture of the response in terms of biochemical and regulatory processes is emerging. A challenge is to find out more about the function of these newly identified gene products, and how they contribute to flooding tolerance. Our approach has been to manipulate levels of candidate gene products (using sense and antisense constructs) in the model system Arabidopsis thaliana, combined with biochemical and phenotypic analysis of the resulting transgenic plants.